The online regulation of no-vision walking in typically calibrated and recalibrated perceptual-motor states examined using a continuous pointing task - Burkitt, James (My University, 2017)
No-vision walking is supported in the central nervous system (CNS) by a spatial updating process. This process involves the iterative updating of a mental representation of the environment using estimates of distance traveled gleaned from locomotive kinematic activity. An effective means of examining the online regulation of this process is a continuous pointing task, which requires performers to walk along a straight-line forward trajectory while keeping their right arm straight and index finger fixated on a stationary ground-level target beside the walking path. In the current thesis, no-vision continuous pointing was examined in typically calibrated and recalibrated perceptual-motor states. Shoulder and trunk joint angles provided the basis for perceptual measures that reflected spatial updating performance and kinematic measures that reflected its underlying CNS online regulation. In the typically calibrated conditions, no-vision walking demonstrated a slight perceptual underestimation of distance traveled (Study 1). In the recalibrated conditions, no-vision walking demonstrated: a) perceptual underestimation and overestimation following adaptation periods involving walking with low and high visual gains, respectively (Study 2); and b) partial recalibration following exposures to vision and arm gains (Study 3). The latter was suggested as being impacted by task specific changes in CNS multisensory integration resulting from the development of a robust task prior and/or the altering of sensory cue weights. Importantly, this thesis used a novel trajectory parsing procedure to quantify discrete CNS perceptual updating units in the shoulder plane of elevation trajectory. The starts and ends of these updating units were consistently timed to the late left-to-early right foot swing phase of the step-cycle, regardless of perceptual-motor state. This was suggested to reflect perceptual units that were purposely timed, but indirectly mapped, to this kinematic event. The perceptual differences in Studies 1 and 2 were at least partially reflected in these units.
Keywords: Motor Behaviour; Motor Control; Sensory Recalibration; Virtual Reality; Locomotion; Blind walking; Continuous pointing; Walking; Sensory adaptation